2016
DOI: 10.1002/hfm.20650
|View full text |Cite
|
Sign up to set email alerts
|

Using Ergonomic Risk Assessment Methods for Designing Inclusive Work Practices: A Case Study

Abstract: In common with many industries, manufacturing faces the challenge of effective management of a diverse workforce. Humans differ greatly, but traditional manufacturing work practices do not take into account human variability issues during the work design process. Variations in individual and organizational work performance are due to many individual factors, such as age, gender, level of skill, experience, and background bring performance inconsistencies. This research investigates the effects of individual sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 3.1.3.4 87 ) Poland 2016 Application of the OWAS in automobile industry workers. 3.1.3.6 73 ) England 2016 Application of the OWAS and REBA in a furniture factory workers. 3.1.3.2 99 ) Iran 2017 Application of the OWAS, RULA, REBA, PATH, QEC and Nordic Musculoskeletal Questionnaire, in industry workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 3.1.3.4 87 ) Poland 2016 Application of the OWAS in automobile industry workers. 3.1.3.6 73 ) England 2016 Application of the OWAS and REBA in a furniture factory workers. 3.1.3.2 99 ) Iran 2017 Application of the OWAS, RULA, REBA, PATH, QEC and Nordic Musculoskeletal Questionnaire, in industry workers.…”
Section: Resultsmentioning
confidence: 99%
“…On the last available study, Hussain et al 73 ) studied how the workers abilities influenced in a furnishing factory on their tasks, and made an evaluation of the postures using OWAS y REBA 16 ) . This showed that a 33% of the postures were grave and an immediate correction was suggested.…”
Section: Resultsmentioning
confidence: 99%
“…In sand-dredging operations in Udupi (India) [78], the REBA method, with a 12-point assessment, advised immediate intervention to reduce injuries, specifically in the lower back, as did the assessment by Hanson et al [73] in manual collection operations. Furthermore, recent studies in the United Kingdom [74] gathered information on the effects of individual skills on job performance and safety in the workplace as well as human well-being, to design more inclusive work practices. Table 6 shows the four publications that have applied REBA individually or collectively in the study of forced postures related to transportation and storage.…”
Section: Production Linesmentioning
confidence: 99%
“…Before the onset of WMSDs, workers suffer a period of muscle soreness or fatigue. If ergonomics analysis tools (EATs) can be used to identify adverse factors or assess the exposure to risk factors for WMSDs in the work design stage, the incidence of WMSDs can be effectively prevented (Álvarez‐Casado, Zhang, Sandoval, & Pedro, ; Capodaglio, ; Hussain, Case, Marshall, & Summerskill, ). Many qualitative and quantitative EATs are available to assess the risk of exposure on site (Hignett & McAtamney, ; Karhu, Härkönen, Sorvali, & Vepsäläinen, ; McAtamney & Corlett, ; Moore & Garg, ; Pascual & Naqvi, ).…”
Section: Introductionmentioning
confidence: 99%